2021
DOI: 10.3389/fbioe.2021.695710
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Fabrication of Human Amniotic Membrane Zinc Oxide Nanoparticles and the Wet/Dry HAM Dressing Membrane for Wound Healing

Abstract: Graphical AbstractFlow chart depicting the methods, preparing, and characterizing, by histological, and scanning electron microscopy, of wet (PW-HAM) and dry (PD-HAM)of wound healing dressing, and preparation of nanoparticles (HAMP ZnO NP); and application of HAM wound dressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Twenty-one days after surgery, the development of functional epithelium on the conjunctival surface was complete, and the HAAM appeared to dissolve and disappear. One month later, the wound in the operative area was completely healed [ 16 ]. Additionally, the full-thickness auricular skin defects [ 20 ] and bone/dental regeneration [ 83 ] verified the above conclusions, meaning that HAAM is an ideal biological dressing for facial wounds.…”
Section: Clinical Applications Of Haammentioning
confidence: 99%
“…Twenty-one days after surgery, the development of functional epithelium on the conjunctival surface was complete, and the HAAM appeared to dissolve and disappear. One month later, the wound in the operative area was completely healed [ 16 ]. Additionally, the full-thickness auricular skin defects [ 20 ] and bone/dental regeneration [ 83 ] verified the above conclusions, meaning that HAAM is an ideal biological dressing for facial wounds.…”
Section: Clinical Applications Of Haammentioning
confidence: 99%
“…This produced composite had strong antibacterial properties on the formation and thickness of gram-negative (S. aureus, S. mutans, E. faecalis, and L. fusiformis) and grampositive (S. sonnei, P. aeruginosa, P. Vulgaris, and C. freundii) bacterial biofilms. 62 Other amniotic membrane-derived tissue engineered constructs Amnion, amnion homogenate, amnion powder, or lyophilized amnion has been combined with other natural or synthetic materials to reach a desirable scaffold for tissue engineering in various studies. Hybrid scaffolds are widely evaluated in tissue engineering.…”
Section: Amniotic Membrane-based Nanoparticlesmentioning
confidence: 99%
“…This produced composite had strong antibacterial properties on the formation and thickness of gram-negative ( S. aureus, S. mutans, E. faecalis, and L. fusiformis ) and gram-positive ( S. sonnei, P. aeruginosa, P. Vulgaris, and C. freundii ) bacterial biofilms. 62…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various kinds of antibacterial metal nanoparticles, like silver nanoparticles, zinc oxide nanoparticles, and titanium oxide nanoparticles, have been incorporated into membranous ECM scaffolds to produce advanced wound dressings (Table 2) [100][101][102]114,115]. Among them, silver nanoparticles have been widely used in the treatment of acute and chronic wounds.…”
Section: Loading With Antibacterial Agentsmentioning
confidence: 99%
“…Zinc oxide nanoparticles, another frequently used agent to avoid wound infection, are compatible with biological system, and their biocompatibility and antimicrobial activity are related to the particle size [116]. After loading with zinc oxide nanoparticles, it was observed that AAM wound dressings showed a dose-dependent antibacterial activity of Gram-positive (S. mutans, S. aureus, L. fusiformis, and E. faecalis) and Gram-negative bacteria (P. vulgaris, S. sonnei, C. freundii, and P. aeruginosa) [102]. In addition to drugs and nanoparticles, antiseptic peptides have been utilized to generate antibacterial biomaterials for wound healing.…”
Section: Loading With Antibacterial Agentsmentioning
confidence: 99%